Scientific and Methodical Basis of Management of Loads in Physical Education and Public Sports Health - Mukhametov Akhmad Mukhametovich (Zien Journals, 2022)
This article discusses the scientific and methodological basis for the standardization of workload in physical education and mass sports. Physical culture also acts as one of the important means of solving the main problem of mankind - the preservation and maintenance of people's lives. Society does not have other adequate means for the physical preparation of people for work and life in general.
Keywords: physical education; mass sports; fitness; training